The Association Between Dietary Patterns and Nutritional Status of Primary School Children in Lowokwaru District, Malang City, Indonesia - Ahmad Rizk Pratama; Siti Nur Aisyah; Emily Jane Thompson (Lembaga Publikasi Ilmiah Nusantara, 2026)
Dietary patterns play a crucial role in determining the nutritional status of primary school children, particularly in developing countries undergoing rapid nutritional transitions. Indonesia continues to face a double burden of malnutrition, where undernutrition and overnutrition coexist among school-aged children. This study aims to examine the association between dietary patterns and the nutritional status of primary school children in Lowokwaru District, Malang City, Indonesia. A cross-sectional study was conducted involving 210 students aged 9–12 years selected using stratified random sampling from public primary schools. Dietary patterns were assessed using a semi-quantitative food frequency questionnaire, while nutritional status was determined based on BMI-for-age Z-scores following WHO standards. Data were analyzed using descriptive statistics and chi-square tests. The results showed a significant association between dietary patterns and nutritional status (p < 0.05). Children with balanced dietary patterns were more likely to have normal nutritional status, whereas unhealthy patterns characterized by high consumption of energy-dense, nutrient-poor foods were associated with overweight and obesity. These findings are consistent with previous studies conducted in various regions of Indonesia and other countries. In conclusion, dietary patterns significantly influence the nutritional status of primary school children. Nutrition education interventions targeting healthy eating habits are urgently needed to improve child health outcomes.